Venus Antiqua Clamshell-Derived Calcium Oxide Nanoparticles for the Preparation of Pla/D-Limonene/Cao Nanocomposites with Antimicrobial Properties - Zapata-Ramirez, P; Loyo-Davila, C; Moreno-Serna, V; Lopez-Toro, E (American Chemical Society, 2023)
Antimicrobial films based on poly(lactic acid) (PLA)/d-limonene/calcium oxide (CaO)-based nanocomposites were prepared by extrusion and successive thermocompression. d-Limonene was incorporated into PLA at a concentration of 5 or 10 wt %. Venus antiqua clamshell-derived calcium oxide (CaO) nanoparticles with an average diameter of 11.2 ± 9.9 nm were added at concentrations of 3 and 5 wt %. A decrease in the glass transition temperature (Tg) by ca. 20% corroborated the plasticizing effect of d-limonene compared to pure PLA. The incorporation of 5 wt % CaO in PLA composites promoted a ca. 15% decrease in Tcc. Although CaO induced a lower Young’s modulus and a lower thermal stability in nanocomposites, excellent antimicrobial performance was demonstrated. Both PLA/limonene and PLA/limonene/CaO films reached 99.99% efficiency against Escherichia coli, regardless of the source of irradiation, d-limonene, and nanoparticle loading. Therefore, these nanocomposites establish significant progress in developing sustainable antimicrobial materials in the fields of medicine or food packaging. © 2023 American Chemical Society.